LITERASI DIGITAL SEBAGAI SARANA PENINGKATAN KECAKAPAN MASYARAKAT DESA DALAM PENGGUNAAN DOMPET DIGITAL DAN BERMEDIA SOSIAL DI ERA GLOBAL - Rahayu, Sri; Kilin, Mochammad Agus Dharma; Nurohman, Ilman; Bunyamin, Wahyu; Imaduddin, Renaldy Azhari; Wahid, Adam Abdul; Mubarok, Muhammad Hilmi Syahrul; Palaha, Fahmi Hadi; Amal, Muhammad Bambang Ikhlasul; Fitria, Dari; Fatwa, Joharudin Muhamad; Latifah, Sufi; Jaelani, M Jidan Jibran; Solihah, Ilmi; Sinta, Ajeng Rustiani; Ramdhani, Galang; Husaeni, Deden Hilmi; Nurjaman, Ahmad; Rusmana, Azqia Fhairiza; Azima, Tubagus Mulkan (Institut Teknologi Garut, 2023)
The aim of this research is to determine the development and level of understanding of the Mekarsari village community regarding the importance of Digital Literacy culture in the global era. One of the efforts made is through Real Work Lecture (KKN) activities in which there are door to door activities regarding understanding digital wallets and digital ethics. and digital literacy seminar activities in villages, these activities are supported by the Ministry of Communication and Information (KOMINFO) to encourage the acceleration of development in villages and improve the quality of human resources in villages through the use of digital wallets and social media. Ministry of Communication and Informatics KOMINFO with a minimum target of 300 literate people using seminars and door to door methods directly to residents. The door to door results in Mekarsarari village showed that the number of people who were literate was 245 people, while the number of people who took part in the digital literacy seminar was 152 people.